The Warwick Hip Trauma Evaluation One – an abridged protocol for the WHiTE One Study: An embedded randomised trial comparing the X-bolt with sliding hip screw fixation in extracapsular hip fractures. Issue 10 (October 2013) - Griffin, X. L.; McArthur, J.; Achten, J.; Parsons, N.; Costa, M. L.
Abstract : Fractures of the proximal femur are one of the greatest challenges facing the medical community, constituting a heavy socioeconomic burden worldwide. Controversy exists regarding the optimal treatment for patients with unstable trochanteric proximal femoral fractures. The recognised treatment alternatives are extramedullary fixation usually with a sliding hip screw and intramedullary fixation with a cephalomedullary nail. Current evidence suggests that best results and lowest complication rates occur using a sliding hip screw. Complications in these difficult fractures are relatively common regardless of type of treatment. We believe that a novel device, the X-Bolt dynamic plating system, may offer superior fixation over a sliding hip screw with lower reoperation risk and better function. We therefore propose to investigate the clinical effectiveness of the X-bolt dynamic plating system compared with standard sliding hip screw fixation within the framework of a the larger WHiTE (Warwick Hip Trauma Evaluation) Comprehensive Cohort Study. Cite this article: Bone Joint Res 2013;2:206–9.